2017
DOI: 10.1139/cjpp-2016-0693
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen potentiates beneficial anti-infarct effect of hypoxic postconditioning in isolated rat hearts: a novel cardioprotective intervention

Abstract: Keyword:Ischemia-reperfusion injury, ischemic postconditioning, hypoxic postconditioning, molecular hydrogen, antioxidants https://mc06.manuscriptcentral.com/cjpp-pubs AbstractGeneration of free radicals through incomplete reduction of oxygen during ischemia/ reperfusion is well-described. On the other hand, molecular hydrogen (H 2 ) reduces oxidative stress due to its ability to react with strong oxidants and easily penetrate cells by diffusion, without disturbing metabolic redox reactions. This study was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…For example, the lipid peroxidation product, 4-hydroxy-2-nonenal, in cardiomyocytes mediates the Nrf2-dependent upregulation of uncoupling protein 3 (UCP3) [135]. This effect might be particularly important in mediating the protective effects of pre-conditioning, which induces mild oxidative stress and subsequent upregulation of various proteins including cytokines, heat-shock proteins, NF-κB, and Nrf2 [8,136,137,138]. This process of a stress being mildly toxic followed by increased cellular protection is referred to as hormesis [139].…”
Section: New Approach For Prevention and Treatment Of Cardiovasculmentioning
confidence: 99%
“…For example, the lipid peroxidation product, 4-hydroxy-2-nonenal, in cardiomyocytes mediates the Nrf2-dependent upregulation of uncoupling protein 3 (UCP3) [135]. This effect might be particularly important in mediating the protective effects of pre-conditioning, which induces mild oxidative stress and subsequent upregulation of various proteins including cytokines, heat-shock proteins, NF-κB, and Nrf2 [8,136,137,138]. This process of a stress being mildly toxic followed by increased cellular protection is referred to as hormesis [139].…”
Section: New Approach For Prevention and Treatment Of Cardiovasculmentioning
confidence: 99%
“…The role of H 2 was found in hypoxic postconditioning, radiation-induced heart injury, mediastinal irradiation in rats, acute cardiac injury, radiation-induced heart disease and changes in microRNA-1, -15b and -21 levels in irradiated rat hearts. [17][18][19][20][21][22] Beneficial effect of H 2 in clinical medicine was found in various diseases, such as cardiovascular diseases, type 2 diabetes, dyslipidemia, obesity and metabolic syndrome, in vascular health. [23][24][25] Molecular hydrogen water improved the progression of Parkinson´s disease.…”
Section: Discussionmentioning
confidence: 99%
“…27 H 2 protects antioxidant enzyme -superoxide dismutase. 22 Molecular hydrogen effect on other antioxidant -coenzyme Q (CoQ) -is not known up to now.…”
Section: Discussionmentioning
confidence: 99%
“… 52 A research in 2017 demonstrated that compared with hypoxic postconditioning (HpostC) alone, the combined cardioprotective effect of hydrogen and HpostC could be better brought into play, which showed up as the reduction of infarct size, the attenuation of severe arrhythmias, and the improvement of heart function. 53 Another study showed that hydrogen inhalation during percutaneous coronary intervention was feasible and could also promote left ventricular reverse remodeling at 6 months after ST-elevated myocardial infarction, which was the first clinical research of hydrogen on percutaneous coronary intervention surgery for myocardial infarction. 54 However, the limited subjects could not determine the therapeutic effect of this method for sure, which need to be further confirmed.…”
Section: T He R Esearch P mentioning
confidence: 99%